(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In the history of India, we can see many social reformers and thinkers who thought for the emancipation of women, freedom and to remove their injustice in every era. Mainly in the nineteenth and twentieth century’s, it can be seen that many social reformers and intellectuals have put forward the idea of women’s liberation in a real sense and have greatly enlightened the society. It is also seen that the work of women’s rescue has been done in that regard. It is seen that women are included in a large amount; they have done social movements to get justice and rights. Raja Ram Mohan Roy has to be credited with starting the movement for emancipation of female slavery in modern India. He enlightened the Indian society with strong thoughts against all bad practices. Mahatma Gandhi expressed his views in favor of women and opined that women should actively participate in the movement along with men. Revolutionary men have contributed as much as women revolutionaries in the Indian freedom movement. Many Indian women took up many social movements to break the injustice and challenge the dominance of men. Through this movement, they brought forward social awareness and women liberation. Therefore, the women’s movement in India was successful in establishing social equality in many ways.